2001
DOI: 10.1016/s0008-6215(00)00307-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid state NMR and X-ray diffraction studies of α-d-galacturonic acid monohydrate

Abstract: Crystalline a-D-galacturonic acid monohydrate has been studied by 13 C CPMAS NMR and X-ray crystallography. The molecular dynamics were investigated by evaluating 13 C spin-lattice relaxation in the rotating frame (T 1r ) and chemical-shift-anisotropy properties of each carbon. Only limited molecular motions can be detected in the low frequency (B 10 4 Hz) range by 13 C relaxation time measurements (T 1r ) and changes of chemical shift anisotropy properties as a function of temperature. X-ray analysis (at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
(49 reference statements)
3
16
0
Order By: Relevance
“…Similar effects were also observed for methyl a-d-glucopyranoside [31], glycosylated a-tocopherols [32], galacturonic acid [16,17] and its methylated derivatives [17]. Such differences probably result from the differences in the H-bond patterns in the solution and solid state.…”
Section: Solid-state Nmr Studies Of Cellobiose Motionssupporting
confidence: 63%
See 2 more Smart Citations
“…Similar effects were also observed for methyl a-d-glucopyranoside [31], glycosylated a-tocopherols [32], galacturonic acid [16,17] and its methylated derivatives [17]. Such differences probably result from the differences in the H-bond patterns in the solution and solid state.…”
Section: Solid-state Nmr Studies Of Cellobiose Motionssupporting
confidence: 63%
“…Using galacturonic acid and its methyl derivatives as model systems for pectin, we found that the proton relaxation pathways in galacturonic acid, the monomer of pectin backbone, were mainly motions of hydroxyl groups and water of crystallisation [16,17]. No significant pyran ring motion was detected [17] in the crystalline form.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The difference D provides an information about conformational flexibility of molecules. It can also reflect changes in intra-or intermolecular interactions such as hydrogen bonding involving hydroxyl groups or water of crystallization [47]. For the flexible fragments, like O-C6 0 -C5 0 , high D values are observed (up to 4.4 ppm), and for the rigid parts (pyranose skeleton, aromatic ring) D does not exceed 0.5 ppm.…”
Section: Solid-state Nmrmentioning
confidence: 99%
“…The IR spectra of the free acids show very strong bands in the 3450-3200 cm À1 range assigned to strongly hydrogen bonded OH groups [32] that are present in the crystal structure of galacturonic acid [33]. The shift of OH stretching vibrations toward higher frequencies is due to the general weakening of strong sugar hydrogen bonding system upon acid metalation, as observed in Mg(II) and Ba(II) complexes of D-glucuronic acid [34].…”
Section: Ir Spectroscopymentioning
confidence: 99%